Human Diet Patterns During the Qijia Cultural Period: Integrated Evidence of Stable Isotopes and Plant Micro-remains From the Lajia Site, Northwest China - Ma, Zhikun; Liu, Shu; Li, Zhao; Ye, Maolin; Huan, Xiujia (Frontiers in Earth Science, 2022)
The diet of prehistoric humans in the Qijia period (4,400-3,500 BP) was significantly changed by the advent of dry agriculture and food globalization. However, it is yet to be proven whether wild plants were exploited despite the cultivation of millet, and whether wheat crops, cattle, and sheep originating from southwestern Asia were adopted into the regional human diet. This study presents stable isotope, starch grain, and phytolith analyses of 24 human teeth from the Lajia site in Qinghai, which is a representative Qijia culture settlement site. The carbon and nitrogen isotope results show that the subjects primarily ate C4 plants and had a high protein diet. Starch grain and phytolith results showed that the inhabitants consumed broomcorn millet (Panicum miliaceum), foxtail millet (Setaria italica), Triticeae, tubers and roots, along with other Pooideae and Poaceae plants. This data proves that although broomcorn and foxtail millet formed the mainstay of the Qijia diet, it also included a wide range of plants, such as the tribe Triticeae, tubers and roots, which would have been foraged rather than grown. Compared with the other three contemporaneous sites in Northern China, the proportion of millet starches was highest at the Lajia site, while the type and proportion of foraged plants were the lowest. This was probably because of the arid environment in the region, which could not have supported sufficient plant resources for foraging, which in turn might have led to enhanced millet cultivation and/or a greater reliance on hunting. No wheat or barley traces were found in human teeth in Lajia, and the high proportion of nitrogen was possibly related to the consumption of sheep because sheep bones were found in a zooarchaeological study. This study enhances our understanding of the subsistence strategies present in Qijia culture and of prehistoric food globalization, which is of pivotal significance for a deeper understanding of interactions between east and west Asia during the Neolithic and Bronze ages.